2001
DOI: 10.1007/s002590100601
|View full text |Cite
|
Sign up to set email alerts
|

An original approach in the diagnosis of early breast cancer: use of the same radiopharmaceutical for both non-palpable lesions and sentinel node localisation

Abstract: A modern approach to the surgical treatment of early breast carcinoma requires intraoperative localisation of non-palpable lesions and assessment of the lymph node status. Localisation of breast lesions can be achieved by intratumoural injection of a small amount of radiotracer and intraoperative use of a gamma probe (i.e. radioguided occult lesion localisation, or ROLL). Assessment of the lymph node status is possible by means of the sentinel node approach. To date, two different radiopharmaceuticals have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 25 publications
4
40
0
12
Order By: Relevance
“…For all these reasons, ROLL is an important development in breast cancer treatment. has been injected to confirm the position by preoperative mammography [3]. Recently, the original technique has been simplified performing the localisation without breast scintigraphy or contrast medium injection and mammography [4,5].…”
Section: The Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…For all these reasons, ROLL is an important development in breast cancer treatment. has been injected to confirm the position by preoperative mammography [3]. Recently, the original technique has been simplified performing the localisation without breast scintigraphy or contrast medium injection and mammography [4,5].…”
Section: The Techniquementioning
confidence: 99%
“…All studies evaluating ROLL has concluded it as easy and accurate method for a surgeon to find an occult breast lesion and excise it adequate free tissue margins [2][3][4][5][6][7][8][9]11,12]. According to our experience, tumour localisation has been successful in all cases and at least 4 mm free margins have been achieved in over 90% of cases after the completion of the primary operation [4].…”
Section: The Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan çalışmaların çoğunda radyonüklid madde ile işaretlemenin güvenilir ve etkili olduğu kanıtlanmıştır (17,26,28,29,(35)(36)(37)(38)(39). Radyonüklid madde ile işaretlemede başarı oranları literatürde %92 ile %100 arasında değişmektedir (17,25,36,39,40). Bizim serimizde de işaretlemede başarı oranı %100 dür.…”
Section: Tartışma Ve Sonuçlarunclassified
“…This means that by altering the sensitivity on the gamma probe it is possible to differentiate between radioactive emissions from the localized lesion and the sentinel lymph nodes irrespective of the site of the primary lesion, although the benefit of this has not been confirmed in RCTs. The range for successful identification of the sentinel lymph node for RSL is between 96.8 % [14] and 100 % [15,16], whereas, the same figure for ROLL is between 84.9 % [28] and 100 % [12,22,37]. This would suggest a trend towards favouring RSL for successful sentinel lymph node biopsy (SLNB) over ROLL.…”
mentioning
confidence: 99%